Implementation Of the Waihawa Community Traditional Marriage Service from Social Cultural Aspects in Waihawa Village - Edivildus, Avitus; Nuwa, Gisela; Kasim, Abdullah Muis (Jurnal Riset Ilmu Pendidikan, 2022)
Traditional marriage is actually a bond between men and women who are united through traditional marriage rituals by going through various stages in the custom, as a legal customary marriage process between husband and wife. Customary marriage is not only a bond between husband and wife, but involves the entire extended family of both parties, relatives and tribes or clans who are part of the members of the couple legalized in the customary marriage. Through traditional marriages, kinship and kinship relations are increasing and increasingly displaying a social relationship that creates a familial bond between the two parties. This kinship and kinship relationship is a sign that customary marriage is not only legalizing husband and wife but more than that, embracing the big family and the relationships in the social life of the community become full of brotherly bonds with each other. With traditional marriages that are structured in an area, it is proof that the community is able to maintain and preserve the value of the traditional marriage in social life and is able to provide education to the community and the younger generation to maintain the elements and values ??contained in the traditional marriage. In the midst of increasingly rapid developments, the role of indigenous peoples has become more active in maintaining the nobility of these customary values. Therefore, the participation of all parties in social groups is important because without the involvement of all parties from within the family, community, tribal/clan members, local government and customary stakeholder institutions as well as society in general in social groups, so that cultural heritage cannot be lost. only belongs to individuals but belongs to all people in social groups, because it is a sign and identity of every community in social life.